Seeing is believing: good graphic design principles for medical research. (25th June 2015) - Duke, Susan P.; Bancken, Fabrice; Crowe, Brenda; Soukup, Mat; Botsis, Taxiarchis; Forshee, Richard; Bretz, Frank
<x xml:space="preserve">Abstract</x> Have you noticed when you browse a book, journal, study report, or product label how your eye is drawn to figures more than to words and tables? Statistical graphs are powerful ways to transparently and succinctly communicate the key points of medical research. Furthermore, the graphic design itself adds to the clarity of the messages in the data. The goal of this paper is to provide a mechanism for selecting the appropriate graph to thoughtfully construct quality deliverables using good graphic design principles. Examples are motivated by the efforts of a Safety Graphics Working Group that consisted of scientists from the pharmaceutical industry, Food and Drug Administration, 1 and academic institutions. Copyright © 2015 John Wiley & Sons, Ltd.